2017
DOI: 10.1002/bmc.4145
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a simple solid‐phase extraction method coupled with liquid chromatography–triple quadrupole tandem mass spectrometry for simultaneous determination of lincomycin, tylosin A and tylosin B in royal jelly

Abstract: We have developed an analytical method for the determination of lincomycin, tylosin A and tylosin B residues in royal jelly using liquid chromatography-triple quadrupole tandem mass spectrometry analysis. For extraction and purification, we employed 1% trifluoroacetic acid and 0.1 m Na EDTA solutions along with an Oasis HLB cartridge. The target antibiotics were well separated in a Kinetex EVO C reversed-phase analytical column using a combination of 0.1% formate acid in ultrapure water (A) and acetonitrile (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The sensitivities of three other analytical columns (Phenomenex Kinetex ® EVO C 18 , Luna ® C 18 and Gemini ® ‐NX C 18 ) were compared. The Gemini‐NX C18 column produced superior results with sharp peaks and showed better chromatographic separation than the other columns (Zheng, Park, Abd El‐Aty et al, ).…”
Section: Resultsmentioning
confidence: 96%
“…The sensitivities of three other analytical columns (Phenomenex Kinetex ® EVO C 18 , Luna ® C 18 and Gemini ® ‐NX C 18 ) were compared. The Gemini‐NX C18 column produced superior results with sharp peaks and showed better chromatographic separation than the other columns (Zheng, Park, Abd El‐Aty et al, ).…”
Section: Resultsmentioning
confidence: 96%
“…In comparison with various methods (Table 7), the first four ways of sample preparation were simple and fast, which used liquid extraction and a dilution step prior to direct injection into the instrument, but there was a high risk of mass spectrometry source contamination due to injecting “dirty” extracts. Compared with the last three approaches using magnetic molecularly imprinted polymers or commercial SPE cartridges (Oasis HLB cartridge and Bond-Elut C18 SPE cartridge) [5, 24, 50], the developed method in this work exhibited lower LODs and higher recoveries.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, as the duck meat matrix has a fat content, n ‐hexane was employed to extract the fatty acids (Zheng et al, ). In addition, previous studies (Hamscher, Sczesny, Höper, & Nau, ; Yang, Cha, & Carlson, ; Zheng, Park, Abd El‐Aty, Kim, Cho, Choi, et al, ) reported that the addition of Na 2 EDTA is necessary to prevent complexation of the tetracyclines and macrolides with metal ions, which could lead to low recoveries; therefore, SPE methods with and without Na 2 EDTA were assayed for comparison. As shown in Figure , low recoveries of 32–38 and 35–47% were achieved for tetracyclines and macrolides, respectively, by the SPE method without Na 2 EDTA (concentration: 50 μg/kg, n = 3).…”
Section: Resultsmentioning
confidence: 99%